Effects of neuromuscular fatigue resulting from repeat sprint exercise among trained cyclists on measures of strength and power performance - Blaisdell, R. B. (2019)
The purpose of this dissertation is to better understand the role of repeated-sprint ability (RSA) and resulting fatigue in cyclists; how it relates to measures of aerobic power and strength and power performance indices- due to the nature of cycling competitions and the necessity of RSA for success.